Exploring students’ perceptions of English grammar learning and its pedagogical implication at Vocational High School - Miftachul Ulumiyah; Agus Gozali (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
Grammar is the system of language which deals with the form and structure of words in making sentences well, therefore grammar plays an important role in English subjects. Yet, many students place grammar as the last choice in English subjects, especially students at Vocational High Schools (VHS) who learn English as English for Specific Purpose (ESP) learners, and they are focused on production skills rather than language skill knowledge (Mahbub, 2019). Therefore this study was held to investigate VHS students’ perceptions of English grammar learning to understand and complete their needs in the class. This study was conducted on a VHS with 112 eleventh graders as the participants. This study obtained quantitative data through a survey by distributing a questionnaire adapted from Xiao (2019), Arif (2016), and Sopin (2015) with three main aspects such as students’ attitudes, students’ learning styles, and grammar teaching method preferred by students in English grammar learning. This study revealed that students at this VHS have positive attitudes toward English grammar learning, they also like guided learning styles, and prefer varied teaching ways from the teacher in learning English grammar.